Penggunaan Instant Messanger Dan Komunikasi Interpersonal Remaja - Primada Qurrota Ayun (JURNAL ILMU SOSIAL, 2016)
Interpersonal communication should ideally in face to face, until the achievement of intimate communication. Instant messenger makes interpersonal communication easier and more efficient. However, it also resulted in less effective communication to occur, because it only uses text messaging as a means to convey a message so frequent miscommunication. This study wanted to see how the use of instant messenger among teenagers in interpersonal communication. The theory used in this study is a Computer Mediated Communication, Ecology Media and Interpersonal Intimacy. The method used in this research is phenomenology. The results of this study indicate that the instant messenger is a medium that is considered to be practical and easy to communicate interpersonally with family, friends, and lovers. Interpersonal communication process through instant messenger can not reach the stage of intimate relationship, because of interactions that occur frequently experienced miscommunication due to an incorrect perception. Interpersonal communication is more effective if it is done face to face. Teens when communicating via instant messenger, tend not to believe and to tell the truth.